Beban Kerja dan Lingkungan dengan Stres Kerja Perawat di Rawat Inap RSJ. Prof. M. Ildrem Sumatera Utara - Evalina Perangin Angin; Zulfendri Zulfendri; Siti Saidah Nasution (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Work stress on nurses is a common problem that often occurs in the world of work. Nurses who care for patients with mental disorders tend to experience higher stress than general nurses. This study aimed to determine the relationship between workload and environment and work stress of nurses. This study used a quantitative cross-sectional approach. This study amounted to 105 mental nurses who served in inpatient with accidental sampling. The results of this study found that the workload of 5 respondents (4.8%) with a light workload, 75 respondents (71.4%) moderate, and 25 respondents (23.8%) heavy. The results of the univariate analysis found 34 respondents (32.4%) who reported that their work environment was in the moderate category and 71 respondents (67.6%) were good. The results of the univariate analysis showed that 6 respondents (5.7%) experienced mild stress, 54 respondents (51.4%) had moderate stress, and 45 respondents (42.9%) experienced severe stress. The results of the bivariate analysis with the Gamma correlation test found a positive significant relationship with a very strong relationship strength (p <0.05, r = 0.916) where as many as 51 respondents (68.0%) experienced moderate workload with moderate work stress and were found a negative significant relationship with a strong relationship strength (p <0.05, r = -0.607) where as many as 42 respondents (59.2%) experienced moderate stress in a good work environment. Researchers suggest that the availability of nurses must be adjusted and the workload given must be adjusted to their capacity, while the work environment requires additional lighting to carry out activities optimally, healthy, safe, and comfortable. Keywords: Workload, work Environment, Mental Nurse Work Stress